Traditional Cantonese diet and nasopharyngeal carcinoma risk: a large-scale case-control study in Guangdong, China - Jia, Wei-Hua (BioMed Central, 2010)
BACKGROUND: Nasopharyngeal carcinoma (NPC) is rare in most parts of the world but is a common malignancy in southern China, especially in Guangdong. Dietary habit is regarded as an important modifier of NPC risk in several endemic areas and may partially explain the geographic distribution of NPC incidence. In China, rapid economic development during the past few decades has changed the predominant lifestyle and dietary habits of the Chinese considerably, requiring a reassessment of diet and its potential influence on NPC risk in this NPC-endemic area. METHODS: To evaluate the association between dietary factors and NPC risk in Guangdong, China, a large-scale, hospital-based case-control study was conducted. 1387 eligible cases and 1459 frequency matched controls were recruited. Odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were estimated using a logistic regression model, adjusting for age, sex, education, dialect, and habitation household type. RESULTS: Observations made include the following: 1) consumption of canton-style salted fish, preserved vegetables and preserved/cured meat were significantly associated with increased risk of NPC, with enhanced odds ratios (OR) of 2.45 (95% CI: 2.03-2.94), 3.17(95% CI: 2.68-3.77) and 2.09 (95% CI: 1.22-3.60) respectively in the highest intake frequency stratum during childhood; 2) consumption of fresh fruit was associated with reduced risk with a dose-dependent relationship (p = 0.001); and 3) consumption of Canton-style herbal tea and herbal slow-cooked soup was associated with decreased risk, with ORs of 0.84 (95% CI: 0.68-1.03) and 0.58 (95% CI: 0.47-0.72) respectively in the highest intake frequency stratum. In multivariate analyses, these associations remained significant. CONCLUSIONS: It can be inferred that previously established dietary risk factors in the Cantonese population are still stable and have contributed to the incidence of NPC.